Calculation of Parameters of Prism Deflector for Laser Scanner - I. E. Gusarov; A. I. Kalugin; M. Yu. Alyes; E. A. Antonov (Приборы и методы измерений)
The prism deflector which is a multifaceted prism with reflective facets is the most common scanning element that allows to quickly fill a wide scanning area with laser radiation pulses along one coordinate. The parameters of a prismatic deflector are related to the characteristics of the laser radiation of the scanned area parameters and of the deflector position, and are also limited by various factors, such as safety requirements or scanning time. The aim of this work was to analyze the relationship between the external operating conditions of a laser scanning system and the internal design parameters of a prism deflector.A variant of calculating of laser pulses frequency by the number of spots and their overlap coefficient is considered. A method for calculating of a prism deflector characteristics based on external parameters, such as the angle of incidence of radiation to the facet and the width of the Gaussian beam with dimensions that are safe for а human eye is proposed. Рrismatic deflectors parameters are proposed depending on the number of reflecting facets. Dependence of a deflector size on the angle of radiation incidence to the reflecting face is shown.When designing a prismatic deflector of a laser scanner used to fill a certain scanning area with the required angular size σ by varying such parameters as the number of faces m and the feed angle α it is possible to achieve optimal deflector characteristics and scanning mode for the task.